2009
DOI: 10.3141/2123-11
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Impacts of High-Emitting Vehicles

Abstract: High-emitting vehicles (HEVs), also known as high emitters, are responsible for a large proportion of total mobile-source emissions, even though they represent a small portion of the total vehicle fleet. Studies conducted in the 1990s indicated that between 7% and 12% of the vehicle fleet accounted for 41% to 63% of total carbon monoxide (CO) emissions; 10% of vehicles were responsible for 47% to 65% of hydrocarbon (HC) emissions; and 10% of vehicles were responsible for 32% of nitrogen oxide (NOx) emissions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…A critical issue in the development of power-generating systems, specifically directed at power systems used in mobile sources, is the improvement and acceptance of on-board diagnostic systems to identify high-emissions vehicles, which can lead to corrective action. As previously stated, a small percentage of improperly operating vehicles are often large contributors to non-CO 2 emissions (70)(71)(72)(73). Under these circumstances, the design of low-emissions fuels should be directed at these poorly operating vehicles with high emissions, which are differentially impacted by fuel www.annualreviews.org • Fuel Design to Reduce Adverse Impacts 5.13 Changes may still occur before final publication online and in print composition (74).…”
Section: Design Criteriamentioning
confidence: 94%
See 1 more Smart Citation
“…A critical issue in the development of power-generating systems, specifically directed at power systems used in mobile sources, is the improvement and acceptance of on-board diagnostic systems to identify high-emissions vehicles, which can lead to corrective action. As previously stated, a small percentage of improperly operating vehicles are often large contributors to non-CO 2 emissions (70)(71)(72)(73). Under these circumstances, the design of low-emissions fuels should be directed at these poorly operating vehicles with high emissions, which are differentially impacted by fuel www.annualreviews.org • Fuel Design to Reduce Adverse Impacts 5.13 Changes may still occur before final publication online and in print composition (74).…”
Section: Design Criteriamentioning
confidence: 94%
“…Several studies in the United States and other parts of the world have shown that 5% to 10% of the vehicles operating on roadways can make up 30% to 75% of the exhaust emissions (70)(71)(72)(73). These high-emissions vehicles include vehicles with improperly working power systems or improperly working emissions control devices and very old or off-market vehicles that were not built to meet contemporary emissions standards.…”
Section: Fuel Utilization By Power Systemsmentioning
confidence: 97%